COVID crash: a study of volatility spillovers from stocks to us indexes and from us indexes to cryptocurrencies - Carvalho, Pedro Maria Fragoso de Almeida (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science